Fabrication of NiCo2O4 and carbon nanotube nanocomposite films as a high-performance flexible electrode of supercapacitors1. Issue 90 (1st October 2015) - Xu, Shanshan; Yang, Deming; Zhang, Fan; Liu, Jiacheng; Guo, Anran; Hou, Feng
<x xml:space="preserve">Abstract</x> Herein, we demonstrated facile fabrication of NiCo2O4 nanoparticles on a CNT film by a chemical deposition method, followed by thermal annealing treatment processing.